Relación de la eritrosedimentación y proteína c reactiva con la ferritinemia en escolares de 8-12 años de la Unidad Educativa Simón Rodríguez de Licán - Orozco Andrade, Valeria Mishel (2018)
The research aims to evaluate acute phase reactants in the students of the Simón Rodríguez de Licán de Riobamba Educational Unit. The study was conducted in patients from 8 to 12 years old. The were 180 schoolchildren. Their blood samples were collected, which were taken with the proper biosafety regulations and the respective informed consent of the legal representatives of the students; Then the biological samples were transported in a suitable parametric way, to wards Research Laboratory of the Faculty of Health Sciences, of the National University of Chimborazo, where hematological, serological and biochemical tests were carried out. A unilabiate descriptive statistical analysis was performed using the square text test to verify the relationship between the tests of erythrocyte sedimentation, C-reactive protein in Ferritinemia. A level of significance p <0.05 was used in all tests with a confidence interval of 95%. The results show that there is no statistically significant relationship between erythrosedimentation and serum ferritin. When only erythrocyte sedimentation rate was related to ferrite, it was not statistically significant to the case of positive C-reactive protein, serum ferritin concentration was higher within the range of normal values; so it states that there is no statistically significant relationship. For this reason it was concluded that there is no relationship between these variables and serum ferritin.